Influence of Store Atmosphere, Product Knowledge and Brand Image toward Purchase Decision through Word of Mouth - Aisah, Iin Nur; Wahyono, Wahyono (Universitas Negeri Semarang, 2018)
Word of mouth has an important role in improving purchase decision that supported with unique and interesting store atmosphere, good product knowledge and positive brand image. However, some previous studies showed different result that by unique and interesting store atmosphere, good product knowledge and positive brand image to word of mouth and purchase decision for the company. The purpose of this study is to examine the direct influence of store atmosphere, product knowledge, and brand image, on Purchasing Decision and its indirect influence through word of mouth. Sample in this study are 115 consumers in the city of Semarang with sampling incidental sampling technique. The analysis technique used path analysis with SPSS program version 21. The result showed that store atmosphere, product knowledge, and brand image had positive effect and significant on purchase decision with significance < 0.05. While the test of intervening obtained by the total value of the indirect > direct effect, that store atmosphere of 0.1519 > 0.142, product knowledge of 0.427 > 0.327, and brand image of 0.5185 > 0.513. The conclusions of this study proved that store atmosphere, product knowledge, and brand image had positive effect and significant on purchase decision by direct effect and indirectly through word of mouth.